Perinatal Oral Health: A Novel Collaborative Initiative to Improve Access, Attitudes, Comfort Level, and Knowledge of Pregnant Women and Dental Providers - Melanie E. Mayberry; Bernard Gonik; Robert M. Trombly (Thieme Medical Publishers, Inc., 2020)
Objectives The objectives of this program were to increase access to dental care among pregnant women and to improve dental students' exposure, comfort level, and knowledge of the potential impact of poor oral health on pregnancy outcomes. Study Design Through collaborative efforts of a School of Dentistry and a School of Medicine, the Oral Health Pregnancy Day Initiative (OHPDI) was developed. Dental students were educated on the impact poor oral health may have on pregnancy outcomes and the importance of access to care. Pregnant women received perinatal oral health education and needed dental care. Results Thirty-four pregnant women presented for the OHPDI. Thirty-nine dental students participated. Eighty-five percent of students reported they learned how poor oral health may have a negative impact on pregnancy and birth outcomes; 79% agreed as a result of the event they were more likely to treat pregnant women. Ninety-four percent of pregnant women reported not having a dentist and 100% received perinatal oral health education and needed dental care. Eighty-eight pregnant women were seen subsequent to the OHPDI. Conclusion This initiative resulted in increased students' knowledge, exposure, and comfort level to treating pregnant women and pregnant women received needed oral health care education and dental treatment.